Bilateral Langerhans Cells Histiocytosis in the Temporal Bone: A case report - Saha, Kanu Lal; Dey, Bishnu Pada; Joarder, Md Abul Hasnat; Haque, Mohammad Anamul; Bhowmik, Bishwajit (Bangladesh Journal of Otorhinolaryngology, 2020)
Langerhans cells histiocytosis (LCH) or histiocytosis-X is a rare group diseases that includes three overlapping diseases of Hand-Schuller-Christian disease (HSC), Letterer-Siwe disease (LS)and Eosinophilic granuloma(EG). It results from clonal proliferation of histiocytes having similar morphology and immunophenotype to Langerhans cells in skin and mucosa Though head and neck manifestation is common, isolated simultaneous bilateral temporal bone Langerhans Cell Histiocytosis is an extremely rare presentation. Having same otological menifestations, high resolution CT scan is advocated for early identification and differentiation of LCH from other common conditions such as mastoidits,otitis externa ,chronic suppurative otitis media. Diagnosis of LCH is confirmed by biopsy and immunohistochemical staining of S-100 protein and or CD1a antigen. Chemotherapy is main mode of treatment.The prognosis is worse when presenting age of children is younger than 2 years. Bangladesh J Otorhinolaryngol; April 2020; 26(1): 68-72